Experimental recombination rate coefficients of B-like carbon and B-like neon - (:unkn) unknown (IOP PUBLISHING LTD, 2013)
In this paper, we present recombination rate coefficients for astrophysically relevant B-like C and B-like Ne ions, recently measured at the CRYRING electron cooler. The investigated energy ranges covered the dielectronic recombination resonances of 2s-2p (Delta n = 0) core excitations for both the ions. The experimental rate coefficients are compared with the results from AUTOSTRUCTURE calculation. Temperature-dependent plasma rate coefficients from 10(3) to 10(6) K are obtained from the recombination spectra by convolution with Maxwell-Boltzmann energy distributions. The experimental plasma rate coefficients of B-like C show good agreement with the calculations at high temperatures, while at low temperatures, the calculated results severely underestimate the plasma rate coefficients. In the case of B-like Ne, the agreement between experimental and calculated results is rather good (within the experimental uncertainties) over the presented temperature range.
Keywords: FINITE-DENSITY PLASMAS; DIELECTRONIC RECOMBINATION; C-II; IONIZATION; IONS; CASSIOPEIA; ELEMENTS; VI